Skill requirements for emerging technologies in Ireland - Whelan, Adele; McGuinness, Seamus; Staffa, Elisa; Egan, Paul (ESRI, 2024)
This research examines the labour market for jobs in Automation, Artificial Intelligence and Blockchain in Ireland.